Effects of pulse current mode on plasma electrolytic oxidation of 7075 Al in Na2WO4 containing solution: From unipolar to soft-sparking regime. (10th September 2018) - Hakimizad, Amin; Raeissi, Keyvan; Santamaria, Monica; Asghari, Mahasta
Abstract: Plasma electrolytic oxidation coatings were produced on 7075 Al alloy in a silicate based solution containing sodium tungstate using unipolar, usual bipolar and soft-sparking bipolar pulsed current regimes. X-ray diffraction proved that the coatings contain gamma alumina and metallic tungsten. EDS results showed that the tungsten content decreases with increasing the negative half cycle. Scanning electron microscopy showed that the pancake and volcano-like were dominant morphologies for the coatings produced by the unipolar and bipolar current regimes, respectively. Under unipolar current regime, a band of large pores is observed at the metal/coating interface, while they became discrete by applying the bipolar current regime and their population decreased significantly with increasing the negative half cycle. The coating produced by soft-sparking regime showed the highest corrosion resistance in chloride containing solution, resulting also very effective toward localized corrosion, due to a synergistic effect of W incorporation and employed waveform. Incorporation of tungsten resulted in the formation of hard coating (up to 1900 Hv) with dark appearance, therefore promising for thermal control applications. Graphical abstract: Image 1 Highlights: By the presence of tungstate, PEO coatings were mainly constituted of Al2 O3 and W. By applying bipolar waveforms, both W and Si contents of the coatings were reduced. The bipolar waveforms produced thicker coatings with dominant volcano morphology. Soft-sparking produced more compact coating with the highest corrosion performance. Coating produced by soft-sparking withstood perfectly against localized corrosion.